Safety of endovascular treatment beyond the 6‐h time window in 205 patients. Issue 6 (7th January 2013) - Jung, S.; Gralla, J.; Fischer, U.; Mono, M.‐L.; Weck, A.; Lüdi, R.; Heldner, M. R.; Findling, O.; El‐Koussy, M.; Brekenfeld, C.; Schroth, G.; Mattle, H. P.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Intra‐arterial treatment (IAT) is effective when performed within 6 h of symptom onset in selected stroke patients ('T < 6H'). Its safety and efficacy is unclear when the patient has had symptoms for more than 6 h ('T > 6H') or for an unknown time (unclear‐onset stroke, UOS), or woke up with a stroke (wake‐up stroke, WUS). In this study we compared the safety of IAT in these four patient groups. Methods Eight‐hundred and fifty‐nine patients treated with IAT were enrolled. The main outcome parameters were clinical outcome [excellent: modified Rankin Scale (mRS) 0 or 1; or favorable: mRS 0–2] or mortality 3 months after treatment. Further outcome parameters were the rates of vessel recanalization, and cerebral and systemic hemorrhage. Results Six‐hundred and fifty‐four patients were treated before (T < 6H) and 205 after 6 h or an unknown time (128 T > 6H, 55 WUS and 22 UOS). NIHSS scores were higher in UOS patients than in T < 6H patients, vertebrobasilar occlusion was more common in T > 6H and UOS patients, and middle cerebral artery occlusions less common in T > 6H than in T < 6H patients. Other baseline characteristics were similar. There was no significant difference in clinical outcome and the rate of hemorrhage in multivariable regression analysis. Conclusions Clinical outcome of our four groups of patients was similar with no increase of hemorrhage rates in patients treated after awakening, after an unknown time or more than 6 h. Our preliminary data suggest that treatment of such patients may be performed safely. If confirmed in randomized trials, this would have major clinical implications.